2018
DOI: 10.1038/s12276-018-0177-z
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin protects endothelial progenitor cells against AGE-induced apoptosis via autophagy flux stimulation and promotes wound healing in diabetic mice

Abstract: Wound healing is delayed in diabetic patients. Increased apoptosis and endothelial progenitor cell (EPC) dysfunction are implicated in delayed diabetic wound healing. Melatonin, a major secretory product of the pineal gland, promotes diabetic wound healing; however, its mechanism of action remains unclear. Here, EPCs were isolated from the bone marrow of mice. Treatment of EPCs with melatonin alleviated advanced glycation end product (AGE)-induced apoptosis and cellular dysfunction. We further examined autopha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
49
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(53 citation statements)
references
References 34 publications
(38 reference statements)
3
49
1
Order By: Relevance
“…AGEs affect normal physiological functions of cells and hinder diabetic wound healing through inducing the production of cytokines and in ammatory factors, inhibiting the generation of collagen, and inducing excessive immune response [35,36]. Therefore, AGEs have been used widely as a stimulant for preparing in vitro models of diabetic wounds [37,38]. Our results con rmed that AGEs signi cantly inhibit the proliferation, migration, and tubular structure formation of HUVECs, whereas KLX signi cantly reverses the inhibitory effect of AGEs.…”
Section: Discussionsupporting
confidence: 57%
“…AGEs affect normal physiological functions of cells and hinder diabetic wound healing through inducing the production of cytokines and in ammatory factors, inhibiting the generation of collagen, and inducing excessive immune response [35,36]. Therefore, AGEs have been used widely as a stimulant for preparing in vitro models of diabetic wounds [37,38]. Our results con rmed that AGEs signi cantly inhibit the proliferation, migration, and tubular structure formation of HUVECs, whereas KLX signi cantly reverses the inhibitory effect of AGEs.…”
Section: Discussionsupporting
confidence: 57%
“…Growing evidence has demonstrated that activation of p38 and JNK signals may lead to MMP-13 expression enhancement (23)(24)(25), whereas NF-kB signaling was also reported to act as a crucial regulator in MMP-13 expression in NPCs (26). Meanwhile, our studies have found that autophagy may also be activated by AGEs and regulate MMP-13 in NPCs (27)(28)(29).These studies above suggest that MAPK, NF-kB signaling, and autophagy may regulate MMP-13 in IVDD, which may also be implicated in diabetic IVDD; however, the relationship between them and BRD4 in diabetic IVDD is still unknown.…”
mentioning
confidence: 51%
“…In a diabetic wound healing model, melatonin improved disrupted wound healing. Therefore, melatonin is suggested to improve disrupted wound healing through inhibiting apoptotic events by stimulation of autophagy pathway [191]. Melatonin also promotes umbilical cord blood (UCB)mesenchymal stem cells (MSCs) motility through enhancing cytoskeletal reorganization which this effect is mediated by melatonin MT2 receptor triggering Gq protein alpha (Gαq)-dependent protein kinase (PK)Cζ phosphorylation regulating Focal adhesion kinase (FAK)/ paxillin-mediated cell division cycle 42 (Cdc42)/actinrelated proteins (Arp2/3) activation [192].…”
Section: Melatonin and Diabetic Wound Healingmentioning
confidence: 99%